2021
DOI: 10.1111/rec.13356
|View full text |Cite
|
Sign up to set email alerts
|

Restoring riparian forest in the Atlantic Forest: does planting seedlings make a difference?

Abstract: Planting seedlings remains the most popular method of forest restoration, but passive restoration may become a new promise to reduce costs, despite concerns about its efficacy. Here, we present a study of a riparian forest recovery program in the Southern Atlantic Forest, Brazil. The objective was to compare planting seedlings and passive restoration eight years since restoration started and assess the influence of cattle presence in the restoring areas. We analyzed the structure, diversity, and composition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 63 publications
0
3
0
1
Order By: Relevance
“…La recuperación de la vegetación en las áreas identificadas de mayor prioridad podría contribuir a reducir la erosión del suelo y deslave en el margen del cauce y zonas adyacentes, a la par de contribuir a la provisión y calidad del agua en la cuenca (Antonini et al, 2022;Naiman et al, 1998). La exclusión del ganado y la siembra de especies de árboles y arbustos nativos para acelerar el proceso de recuperación pueden ser estrategias adecuadas si las condiciones del sitio y el paisaje lo favorecen (Inhamuns et al, 2021;Trujillo-Miranda et al 2018). Por lo tanto, para determinar las técnicas que deben ser prescritas se requieren diagnósticos de las condiciones específicas del sitio.…”
Section: Prioridadunclassified
“…La recuperación de la vegetación en las áreas identificadas de mayor prioridad podría contribuir a reducir la erosión del suelo y deslave en el margen del cauce y zonas adyacentes, a la par de contribuir a la provisión y calidad del agua en la cuenca (Antonini et al, 2022;Naiman et al, 1998). La exclusión del ganado y la siembra de especies de árboles y arbustos nativos para acelerar el proceso de recuperación pueden ser estrategias adecuadas si las condiciones del sitio y el paisaje lo favorecen (Inhamuns et al, 2021;Trujillo-Miranda et al 2018). Por lo tanto, para determinar las técnicas que deben ser prescritas se requieren diagnósticos de las condiciones específicas del sitio.…”
Section: Prioridadunclassified
“…N, F, temperature, dissolved oxygen and electrical conductivity), and iii) water ow abrasion power (Rezende et al 2014a). Also, the vegetation surrounding water bodies plays a fundamental role in supplying organic matter to the aquatic system (Bambi et al 2017), which can undergo anthropogenic alterations due to changes in land use (Bambi et al, 2022;Inhamuns et al, 2021;Brandão et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…terrestrial and aquatic ecosystems(Rezende et al 2019), especially in the less structured riparian vegetation of semi-arid regions(Rezende et al 2018), and emphasize the crucial role of riparian vegetation in ecosystem processes(Inhamuns et al 2021) Higher mass loss was observed in river sections downstream of urban areas compared to those upstream. This result may be related to the higher values of electrical conductivity and turbidity observed in water samples collected downstream of urban areas(Rezende et al 2014a).…”
mentioning
confidence: 98%
“…As the need for and scope of ecological restoration has increased, seed‐based restoration has become a principal method for restoring native plant communities (Broadhurst et al 2008; Merritt & Dixon 2011; Perring et al 2018). Depending on landscape connectivity and land use history, some sites are capable of passive restoration, while others require active restoration via introduction of plant material (Jones et al 2018; Inhamuns et al 2021). Establishment from seed can be considerably less expensive than using plugs (Török et al 2011), and easier to implement quickly at scale.…”
Section: Introductionmentioning
confidence: 99%